(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2024)
Otters, subfamily Lutrinae (Mustelidae), are predators that thrive in aquatic environments, and have a semiaquatic to fully aquatic lifestyle. While modern otters are found across the globe, their fossil history is limited, primarily documented by fragmented dentognathic remains. In this work, we report on and describe new dental remains of a medium-sized Lutrinae from the Late Miocene of Baccinello and Casteani (Tuscany), improving the poor fossil record of the subfamily in Europe. Tyrrhenolutra helbingi Hürzeler, 1987 is a poorly known species, described on some dental remains from the Baccinello mines and a few other localities. Considering its peculiar morphology, it has often been overlooked in the scientific literature. Description of the material stored at the Naturhistorisches Museum, Basel and Museo di Geologia e Paleontologia dell’Università di Firenze offers new insights on the intraspecific variability and dental morphology of this taxon. The comparative study of these findings highlights several morphological and biometrical similarities between T. helbingi and Paludolutra maremmana Hürzeler, 1987, which allow us to redefine these taxa as Tyrrhenolutra maremmana nov. comb. We carried out a total-evidence cladistic analysis seeking support for morphometric and morphological similarities between T. “helbingi” and “P.” maremmana. The resulting parsimony analyses support the synonymy, excluding a close relationship of T. maremmana with Paludolutra of Italy and Spain, as previously thought. Furthermore, we confirm a long-forgotten hypothesis identifying Limnonyx Crusafont Pairó, 1950 as the possible continental ancestor of Tyrrhenolutra.